Planetary Stewardship in an Urbanizing World: Beyond City Limits - Sybil P. Seitzinger; Uno Svedin; Carole L. Crumley; Will Steffen; Saiful Arif Abdullah; Christine Alfsen; Wendy J. Broadgate; Frank Biermann; Ninad R. Bondre; John A. Dearing; Lisa Deutsch; Shobhakar Dhakal; et al. (Ambio, 2012)

Seasonal bioavailability of dissolved organic carbon and nitrogen from pristine and polluted freshwater wetlands - Tracy N. Wiegner; Sybil P. Seitzinger (Limnology and Oceanography, 2004)
We examined the chemical composition and bioavailability of dissolved organic carbon (DOC) and nitrogen (DON) from two pristine and two polluted cedar bog wetlands across three seasons. Pristine and polluted wetlands differed in DOC and DON concentrations, chemical characteristics, and bioavailability. DOC and DON concentrations were higher in the polluted than in the pristine wetlands. In contrast, a higher percentage of the dissolved organic matter (DOM) was more aromatic in the pristine (54% ± 19) than in the polluted (27% ± 4) wetlands. A higher percentage of DOC was bioavailable in the pristine (22% ± 9) than the polluted (12% ± 4) wetlands. A similar percentage of DON was consumed in both the pristine (33% ± 25) and polluted (28% ± 25) wetlands. Seasonally, the bioavailability of DOC and DON varied and differed between the pristine and polluted wetlands. The availability of phosphate appeared to affect the amount of DOC incorporated into bacterial biomass, whereas inorganic nutrient availability did not affect the assimilation of DON. Bioavailable DOC primarily fueled bacterial respiration, whereas DON supported bacterial growth. Overall, our results demonstrate that anthropogenic activities and season affect the quantity and quality of wetland DOM exported to rivers and that different factors control the utilization and fate of DOC and DON within the bacterial community.

Measurement of denitrification in rivers: an integrated, whole reach approach - Andrew E. Laursen; Sybil P. Seitzinger (Hydrobiologia, 2002)

Bioavailability of DON from natural and anthropogenic sources to estuarine plankton - Sybil P. Seitzinger; R. W. Sanders; Renée Styles (Limnology and Oceanography, 2002)
Utilization of dissolved organic nitrogen (DON) from natural (forests) and anthropogenic (animal pastures, urban/suburban storm water runoff) sources (three sites per source) by estuarine plankton communities was examined in spring, summer, and fall. The proportion of DON utilized ranged from 0 to 73%. Overall, urban/suburban storm water runoff had a higher proportion of bioavailable DON (59% ± 11) compared to agricultural pastures (30% 14) and forests (23% ± 19). DON bioavailability varied seasonally; however, the seasonal pattern differed for the three sources. Bacterial production increased linearly with the amount of DON utilized across all sources and seasons; the rate of increase was approximately five times greater per micromole of N as DON used relative to dissolved inorganic N (DIN) used. Although phytoplankton production generally increased with DON addition, the increased production was not correlated with the amount of DON utilized, suggesting that a variable portion of dissolved organic matter (DOM)‐N was directly or indirectly available to the phytoplankton. This indicates that phytoplankton production is not a good measure of the amount of bioavailable DON, and measurements of the amount of bioavailable DON based on bacterial responses alone might not reflect N available to phytoplankton. Preliminary seasonal budgets of bioavailable N (DIN plus bioavailable DON) as a function of land use suggest that ~80% of the total dissolved N (TDN) from urban/suburban runoff is bioavailable, whereas a lower proportion (20–60%) of TDN is bioavailable from forests and pastures. N budgets for aquatic ecosystems based on only DIN loading underestimate bioavailable N loading, whereas total N or TDN budgets overestimate bioavailable N inputs.

Variability in responses to nutrients and trace elements, and transmission of stressor effects through an estuarine food web - Denise L. Breitburg; James G. Sanders; Cynthia C. Gilmour; Colleen A. Hatfield; Richard W. Osman; Gerhardt F. Riedel; Sybil P. Seitzinger; Sybil P. Seitzinger (Limnology and Oceanography, 1999)
Aquatic systems are increasingly exposed to multiple stressors from anthropogenic sources. These stressors can vary in the consistency and magnitude of responses they elicit in biota and in how the presence of additional stressors modifies their effects. Understanding how the biological environment and temporal dynamics influence responses to stressors, and how stressors interact, is important to predicting their effects in the natural environment. We examined temporal variability in responses of an experimental estuarine food web to elevated trace elements and nutrients, as well as non‐additive effects of the combination of these two stressors. Experiments were conducted four times during spring through autumn 1996 in 20 l‐m3 mesocosms. We measured a range of system‐, population‐, and individual‐level parameters to quantify responses of phytoplankton, bacterioplankton, heterotrophic nanoflagellates, copepods, fish, and benthic invertebrates to trace element and nutrient additions. The response to trace element additions was more variable both temporally and among phytoplankton and higher trophic level taxa than was the response to nutrient additions. Most taxa increased, either significantly or showed a trend toward increasing, in response to nutrient additions in all four mesocosm runs. In contrast, the direction as well as the magnitude of responses to trace element additions varied considerably among taxa and experimental runs. Two distinct types of nutrient3trace element interactions were important. First, temporal dynamics of nutrient ratios appeared to affect the temporal pattern of toxicity of trace elements to phytoplankton. Second, in the June mesocosm run when trace element additions reduced production, abundance, or growth of many organisms, these reductions were often proportionately greater in nutrient addition tanks than where no nutrients were added. Our results suggest that considerable temporal and taxonomic variation in responses to trace element loadings are likely to be seen in field settings even under constant loadings to the system and that trace elements may mask the magnitude of the response to high nutrient loadings in eutrophic systems. More generally, the presence of multiple stressors may either increase or dampen the temporal and spatial variability seen in aquatic systems, depending on the interactions among stressors and the influence of background environmental conditions and sensitive species on the expression of stressor effects.

Nitrogen inputs to rivers, estuaries and continental shelves and related nitrous oxide emissions in 1990 and 2050: a global model - Carolien Kroeze; Sybil P. Seitzinger (Nutrient Cycling in Agroecosystems, 1998)